Identification of proteins that interact with mammalian peptide:N-glycanase and implicate this hydrolase in the proteasome-dependent pathway for protein degradation - Park, Hangil (The National Academy of Sciences, 2001)
Peptide:N-glycanase (PNGase) cleaves oligosaccharide chains from glycopeptides and glycoproteins. Recently the deduced amino acid sequence of a cytoplasmic PNGase has been identified in various eukaryotes ranging from yeast to mammals, suggesting that deglycosylation may play a central role in some catabolic process. Several lines of evidence indicate that the cytoplasmic enzyme is involved in the quality control system for newly synthesized glycoproteins. Two-hybrid library screening by using mouse PNGase as the target yielded several PNGase-interacting proteins that previously had been implicated in proteasome-dependent protein degradation: mHR23B, ubiquitin, a regulatory subunit of the 19S proteasome, as well as a protein containing an ubiquitin regulatory motif (UBX) and an ubiquitin-associated motif (UBA). These findings by using the two-hybrid system were further confirmed either by in vitro binding assays or size fractionation assays. These results suggest that PNGase may be required for efficient proteasome-mediated degradation of misfolded glycoproteins in mammalian cells.